EFEKTIVITAS KONSELING KELOMPOK MENGHILANGKAN TRAUMA GUNUNG MERAPI MELETUS MELALUI TEKNIK HUMANISTIK - Fauziah Fauziah; Silvianetri Silvianetri (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2025)
In the event of a disaster, of course there are many things that will affect the victim. Victims will certainly feel trauma, including children, children affected by disasters will of course also feel trauma. With this, there is a need for treatment to reduce feelings of trauma through the application of group counseling with humanistic techniques. This research aims to describe group counseling and humanistic techniques to reduce feelings of trauma in children. This research uses a research method in the form of a literature study. The results of a literature review based on the journals studied reveal that counseling guidance in the form of a group can be the right action in carrying out counseling guidance and humanistic techniques are one way that can be used to reduce the sense of trauma experienced by children.